Under the medical gaze : facts and fictions of chronic pain - Greenhalgh, Susan (University of California Press, 2001)
This compelling account of the author's experience with a chronic pain disorder and subsequent interaction with the American health care system goes to the heart of the workings of power and culture in the biomedical domain. It is a medical whodunit full of mysterious misdiagnosis, subtle power plays, and shrewd detective work.
Keywords: Greenhalgh, Susan -- Health.; Greenhalgh, Susan; Chronic pain -- Patients -- United States -- Biography.; Arthritis -- Patients -- United States -- Biography.; Fibromyalgia -- Patients -- United States -- Biography.; Physician and patient.; Diagnostic errors.; Pain.; Arthritis.; Chronic diseases.; Fibromyalgia.; Pain; Arthritis; Chronic Disease; Diagnostic Errors; Fibromyalgia; Physician-Patient Relations; Douleur chronique -- Patients -- États-Unis -- Biographies.; Fibromyalgie -- Patients -- États-Unis -- Biographies.; Relations médecin-patient.; Erreurs de diagnostic.; Douleur.; Arthrite.; Maladies chroniques.; Fibromyalgie.; HEALTH & FITNESS -- Pain Management.; MEDICAL -- Pain Medicine.; Chronic diseases; Arthritis -- Patients; Chronic pain -- Patients; Diagnostic errors; Fibromyalgia -- Patients; Health; Physician and patient; United States; Chronischer Schmerz; Patient; Fibromyalgie; Rheumatoide Arthritis; Arzt; SOCIAL SCIENCE / Anthropology / General; alternative medicine.; american health care.; biomedical.; chronic disease.; chronic pain.; cultural studies.; detective.; diagnosis.; disease.; ethnography.; feminism.; feminist.; fibromyalgia.; health and wellness.; health care system.; health care.; health issues.; healthy living.; medical issues.; medical science.; medical system.; medicine.; mental health.; pain disorder.; pain management.; physical health.; physical therapy.; psychology.; social studies.; sociopolitical.; therapy.; Personal Narrative; Biography; Personal narratives; Biographies; Personal narratives.; Biographies.; Récits personnels.